2022
DOI: 10.1055/a-1881-4209
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-based diagnosis of abnormalities in small-bowel capsule endoscopy

Abstract: Background Further development of deep learning-based artificial intelligence (AI) technology to automatically diagnose multiple abnormalities in small-bowel capsule endoscopy (SBCE) videos is necessary. We aimed to develop an AI model, to compare its diagnostic performance with doctors of different experience levels, and to further evaluate its auxiliary role for doctors in diagnosing multiple abnormalities in SBCE videos. Methods The AI model was trained using 280 426 images from 2565 patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Previous research has demonstrated that image classification AI models for single lesions in each small bowel CE image can be highly effective. 15,21 Since the image classification process is based on the whole visual feature of an image, image classification AI models are weak in pointing out multiple types of annotations in the same frame.Previous reports using image classification for CE AI rarely mention instances where different annotation types overlap in the same frame. 22 As shown in this study, CE images often contain multiple pathological lesions within the same frame.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that image classification AI models for single lesions in each small bowel CE image can be highly effective. 15,21 Since the image classification process is based on the whole visual feature of an image, image classification AI models are weak in pointing out multiple types of annotations in the same frame.Previous reports using image classification for CE AI rarely mention instances where different annotation types overlap in the same frame. 22 As shown in this study, CE images often contain multiple pathological lesions within the same frame.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that image classification AI models for single lesions in each small bowel CE image can be highly effective 15,21 . Since the image classification process is based on the whole visual feature of an image, image classification AI models are weak in pointing out multiple types of annotations in the same frame.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity was other 99%. The second benefit was reducing reading time from 96.6 AE 22.53 MN with conventional reading to 5.9 AE 2.23 MN with AI [23]. As we reported the next coming step is developing with AI robot allowing with the same capsule automatized stomach and small bowel examination.…”
Section: Artificial Intelligence For Colon Inflammatory Small Bowel D...mentioning
confidence: 90%
“…Deeba et al improved the model by skipping one or a few frames from the sequence of bleeding frames [ 33 ]. A study utilized a CNN-based model to screen high-risk suspicious images from CE videos with a focus on high sensitivity but potentially lower specificity [ 34 ]. Using 84 full-length videos, another study [ 35 ] proposed an algorithm that was comparable with the Suspected Blood Indicator (SBI).…”
Section: Review Findingsmentioning
confidence: 99%